Hubungan Antara Personal Hygiene Dan Status Anemia Dengan Kejadian Infestasi Pediculus Humanus Capitis Pada Santri Kelas 1 Madrasah Tsanawiyah Di Pondok Pesantren “ Assaasunnajah “ Ateuk Lung Ie Kecamatan Ingin Jaya Provinsi Aceh Besar - Dwi Haryatmi (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2024)
Pediculosis humanus capitis is a blood-sucking parasite that spends its entire life cycle on the human scalp. Poor personal hygiene can affect pediculosis capitis infection. In school children, the chronic infestation of pediculosis capitis causes anemia and makes children lethargic and sleepy. The aim of the study was to determine the relationship between personal hygiene and anemia status with the incidence of pediculus humanus capitis in first grade students at madrasah tsanawiyah at the "Assaasunnajah" Islamic boarding school Ateuk lung ie, Wanna Jaya District, Aceh Besar Province. The research design used is descriptive analytic cross sectional approach. The sampling technique of this research is total sampling. The instruments in this study were observation and measurement. Based on the data analysis that has been done, with a total of 30 respondents, poor personal hygiene was obtained by 7 respondents with a percentage of 23.3%. For the incidence of pediculus humanus capitis, 7 respondents stated that a pediculus was found with a percentage of 23.3%. While Anemia Status based on Hb results, 2 respondents were declared Anemia with a percentage of 7%. The conclusion of this study based on the results of the chi square test showed that there was no relationship between personal hygiene and the incidence of pediculus humanus capitis because the test results obtained a p-value of 0.708 > confidence probability of 0.05 and there was a relationship between anemia and the incidence of pediculus humanus capitis in class 1 students of madrasah tsanawiyah at the "Assaasunnajah" Islamic boarding school Ateuk lung ie, Want Jaya District, Aceh Besar Province because the test results obtained a p-value of 0.008 < 0.05 confidence probability. Keywords   : Pediculosis, Pediculosis humanus capitis , Personal hygiene, Anemia